Anti-inflammatory effect of a Nuphar lutea partially purified leaf extract in murine models of septic shock. (23rd February 2015) - Ozer, J.; Levi, T.; Golan-Goldhirsh, A.; Gopas, J.
Abstract: Ethnopharmacological relevance: Various plant organs of Nuphar lutea (L.) SM. (Nymphaeaceae) are used in traditional medicine for the treatment of arthritis, fever, aches, pains and inflammation. The main purpose of this study was to determine the anti-inflammatory effect of Nuphar lutea leaf extract (NUP) in two septic shock models: (1) Survival of mice challenged with a lethal dose of LPS, determination of pro-inflammatory and anti-inflammatory cytokines in serum, as well as in peritoneal macrophages in cell culture. (2) The effect of NUP in a murine model of fecal-induced peritonitis. Materials and methods: NUP pre-treatment partially protected mice in two models of acute septic shock. We concluded that NUP is anti-inflammatory by inhibiting the NF-κB pathway, modulating cytokine production and ERK phosphorylation. Results: A significant average survival rate (60%) of LPS lethally-challenged mice was achieved by pre-treatment with NUP. In addition, NUP pre-treatment reduced nuclear NF-κB translocation in peritoneal macrophages. The production of pro-inflammatory cytokines, TNF-α, IL-6 and IL-12, in the sera of LPS-treated mice or in the supernatants of peritoneal macrophages stimulated with LPS for 2–6 h was also decreased by NUP. Pre-treatment with NUP caused a significant increase in the anti-inflammatory cytokine IL-10. The NUP pre-treatment reduced and delayed mortality in mice with fecal-induced peritonitis. Our studies also revealed that NUP pre-treatment induced a dose-dependent phosphorylation of ERK in peritoneal macrophages. Since most of the reports about the anti-inflammatory effect of Nuphar lutea refer to rhizome and root powder and extracts, it is important to clarify the effectiveness of leaf extract as a source for such activity. Conclusion: NUP pre-treatment partially protected mice in two models of acute septic shock. We concluded that NUP is anti-inflammatory by inhibiting the NF-κB pathway, modulating cytokine production and ERK phosphorylation. Graphical abstract: